Molecular Detection of Helicobacter pylori in Subgingival Biofilm of Patients with Periodontal Disease: A Cross-Sectional Study - Muñoz-Solano, María José (2025)
This cross-sectional observational study aimed to determine the presence of Helicobacter pylori (H. pylori) in the subgingival biofilm (SB) of patients with periodontitis treated at the Clinic of Periodontics of the Faculty of Dentistry of the University of Costa Rica. Fifty-eight patients with periodontitis were recruited. H. pylori antigen detection in stool samples was performed using a qualitative rapid test. SB samples were collected from patients with positive stool results and cultured in Skirrow media, agar tubes, and urea broth under microaerophilic conditions. DNA was extracted and analyzed by polymerase chain reaction (PCR) for H. pylori, and for Porphyromonas gingivalis (P. gingivalis). Of 40 analyzed stool samples, 22 tested positive for H. pylori. Eighteen SB samples from these patients were analyzed. All were urease-positive. H. pylori was detected in all SB studied samples by PCR, colonies could not be isolated on Skirrow media. 16 were PCR-positive from SB, and 14 were PCR-positive from cultures. P. gingivalis was detected in 7 culture samples and 6 SB samples.  Our findings suggest that H. pylori can colonize the subgingival biofilm of patients with periodontitis, as demonstrated through laboratory methods.